Pengembangan E-Modul Hukum Perdata dan Bisnis Berbasis Masalah pada Materi Hukum Perjanjian untuk Mahasiswa S1 Pendidikan Pancasila dan Kewarganegaraan Universitas Negeri Malang - Fauziah, Hamidah Ulfa; Awaliyah, Siti; Hady, Nuruddin (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to develop and test the feasibility, attractiveness, and effectiveness of problem-based civil and business law e-modules. The method used is research and development based on the steps outlined by Borg and Gall. The product developed in this study is an e-module on civil and business law based on contract law material that is feasible, attractive, and effective for students. The feasibility of the product was based on expert validation results of 92 percent for content, 96 percent for media, and 83 percent for learning. The attractiveness test of the product was based on the results of a small-group pilot test at 96.75 percent and a large-group pilot test at 97.58 percent. The effectiveness test of the product was based on the results of a large-group pilot test, with an average pretest score of 57.82, while the post-test score was 72.05. The average score obtained by students in civil and business law courses increased by 14.23.